Governance as network: contradictions and dilemmas. A reflexive perspective. - Francesca Scamardella (Sortuz)
Governance is a term that has come into being recently. It usually indicates practices and procedures that challenge the states’ competences and power. The interest in governance is growing across different social spheres: from economy to politics, crossing environment issues, civil society, and international contexts. Moreover governance seems to be more than a simple trend: actually, according with social sciences, it expresses the transition from a model based on the national and central government, with its forms of hierarchical control, to market and networks, deliberative and organizational processes based on the participation of stakeholders and private actors, as well as public ones. All of these processes arise in a virtual space: the network. Here relationships are horizontal and governed by informal rules; they are organized by cooperation and coordination: all the stakeholder rationally participate to the decision-making-processes, sharing knowledge, power, and means. Does it mean that a governance without government is possible and desirable? The theory of governance as network is fascinating because it gives the idea that in a shared place (the network) it is possible to solve problems through cooperation and coordination amongst actors. Notwithstanding its effectiveness and efficiency, the governance approach poses some problems and dilemmas concerning above all its asserted democratic nature. Can the theory of reflexivity manage these contradictions by developing a serious self-regulation and a responsible and rational metagovernance?